Analysis Of Egg Marketing On Chicken Farming Partnership Pattern in Lamonggedo Jaya Farmer Group Baruga District Of Kendari City - Rinawanti, Rinawanti; Nafiu, La Ode; Sani, La Ode Arsad (Indonesian Journal Of Animal Agricultural Science (IJAAS), 2021)
The research aims to analyze the marketing of eggs in the chicken farming business partnership pattern in the group of farmers Lamonggedo Jaya, Baruga District, Kendari City in December 2020. The object of the study was laying hens as well as all aspects related to egg marketing and determined purposively. Variables in the research in the form of characteristics of respondents, marketing agencies, marketing channels, marketing margins, costs and profits of each marketing institution are analyzed qualitatively and quantitatively. The results of the analysis showed there are four patterns of egg marketing channels, among others, (1) Breeder ïƒ  company ïƒ  great traders ïƒ  retailer merchants ïƒ  end consumer, (2) Breeder ïƒ  company ïƒ  great traders ïƒ  retailer merchants ïƒ  end consumer, (3) Breeder ïƒ  company ïƒ  retailer merchants ïƒ  end consumer, (4) Breeder ïƒ  company ïƒ  end consumer. The highest margin on the 1st marketing channel pattern is Rp. 17,500/shelf, the 4th lowest marketing channel is Rp. 4,000/shelf and the marketing channel in the highest expenditure is the 4th marketing channel Rp. 5,318/shelf. The marketing channel that has the highest profit is the 1st marketing channel Rp. 12.182/shelf. The most efficient marketing channel used by end consumers is the 4th marketing channel because of its lowest marketing margin value.